The Relationship Between Capital Structure and Profitability with Firm Value (A Study of LQ45 Index Companies Listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 Period) - Ni Putu Lilis Febriyanti; Henny Triyana Hasibuan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Firm value is a fundamental indicator of a company's success in generating shareholder wealth and is often presumed to be influenced by various internal factors, including capital structure and profitability. This study aims to empirically examine the relationship between capital structure and profitability with firm value. A quantitative approach was employed using an associative research design. The study population included all companies listed in the LQ45 Index on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. Using a saturated sampling technique, a total of 135 observational data points were initially obtained. After eliminating 12 outlier data points, the final sample consisted of 123 observations. The research utilized secondary data in the form of annual financial statements of the sample companies, which were downloaded from the official IDX website (www.idx.co.id). To test the proposed hypotheses, the data were analyzed using multiple linear regression with the SPSS application. The results show that capital structure does not have a significant relationship with firm value (p-value = 0.064). This finding indicates that, in the context of this study, the company's debt-to-equity composition does not significantly affect its perceived value in the market. However, profitability was found to have a positive and significant relationship with firm value (p-value = 0.003). This suggests that profitability serves as an effective signal for investors in determining firm value, while capital structure does not. In practical terms, company management is advised to focus on enhancing profitability and strengthening business fundamentals, innovation, and good corporate governance as value drivers. Meanwhile, investors are encouraged to conduct a more comprehensive analysis, placing greater emphasis on profitability.